Religious Moderation in Madrasah Ibtidaiyah: A Systematic Review of Contextual Mathematics Learning Strategies - Arfi Wahyu Nurkarim; Ahmad Isroil; Supriyanto Supriyanto; Abdurrahman Rifki (International Journal on Teaching and Learning Mathematics, 2025)
The integration of religious moderation values into mathematics learning in Islamic elementary schools (Madrasah Ibtidaiyah) is a promising approach to simultaneously develop students' character and mathematical reasoning. This study aims to systematically review the strategies and methods used to embed values such as tolerance (tasamuh), justice (i’tidal), balance (tawazun), and deliberation (syura) through contextual mathematics learning. Using a systematic literature review method, this study analyzed peer-reviewed articles, books, and official documents published between 2015 and 2024 across databases such as Google Scholar, DOAJ, and Garuda. Findings indicate that contextual learning especially through open-ended problems, inclusive group projects, and real world applications not only promotes inclusive values but also enhances students' mathematical competence, particularly in reasoning, proportional thinking, and problem-solving. Teachers play a crucial role in designing lessons that address cognitive, affective, and spiritual dimensions. This review provides practical insights for educators and policymakers and identifies future research directions to strengthen integrative models of mathematics education in Madrasah Ibtidaiyah.